The shimmering stone - Harrison, Paula (Harrison, Paula. Rescue princesses, 2013)
In the kingdom of Kamala, Princess Amina is excited her fellow Rescue Princesses are visiting for her cousin's wedding. When a wounded tiger is discovered, she knows the cubs can't survive without their mother. The Rescue Princesses must find them, royal wedding or no royal wedding!